Metagenomic Analysis of a Southern Maritime Antarctic Soil - Pearce, David A.; Newsham, Kevin; Thorne, Michael; Calvo-Bado, Leo; Krsek, Martin; Laskaris, Paris; Hodson, Andy; Wellington, Elizabeth M. (Frontiers in Microbiology, 2012)
Our current understanding of Antarctic soils is derived from direct culture on selective media, biodiversity studies based on clone library construction and analysis, quantitative PCR amplification of specific gene sequences and the application of generic microarrays for microbial community analysis. Here, we investigated the biodiversity and functional potential of a soil community at Mars Oasis on Alexander Island in the southern Maritime Antarctic, by applying 454 pyrosequencing technology to a metagenomic library constructed from soil genomic DNA. The results suggest that the commonly cited range of phylotypes used in clone library construction and analysis of 78-730 OTUs (de-replicated to 30-140) provides low coverage of the major groups present ( 5%). The vast majority of functional genes (>77%) were for structure, carbohydrate metabolism and DNA/RNA processing and modification. This study suggests that prokaryotic diversity in Antarctic terrestrial environments appears to be limited at the generic level, with Proteobacteria, Actinobacteria being common. Cyanobacteria were surprisingly under-represented at 2.6% of sequences, although 1% of the genes identified were involved in CO2 fixation. At the sequence level there appeared to be much greater heterogeneity, and this might be due to high divergence within the relatively restricted lineages which have successfully colonized Antarctic terrestrial environments.